(untitled) (Journal of Face Aesthetics, 2021)
Actinic keratosis (AK) is a common skin disease caused by long-term sun exposure and typically forms on the face, neck, balding scalp, chest and shoulders. AK is characterized by the formation of keratotic macules, papules, or plaques with superficial scales on a red base. Treatment options for actinic keratosis include destructive therapies (eg, surgery, cryotherapy, photodynamic therapy [PDT], dermabrasion), topical medications (eg, diclofenac, topical fluorouracil, imiquimod, ingenol mebutate), and field ablation treatments (eg, chemical peels, laser resurfacing). The aim of this paper was to present a case of patient with AK and the allergic reaction to the 3% diclofenac sodium topical gel ( DSTG) treatment. After a few days of therapy an acute, eczematous reaction on the face was observed. The symptoms have subsided within a week after discontinuing the treatment. The patch test with 3% diclofenac sodium topical gel was performed and evaluated as positive suggesting a delayed type hypersensitivity reaction to active medication or its inactive ingredients. In case of contact allergy confirmed with PT, it is important to inform the patient on the need of future medication avoidance.